Study rates values of the kinetic energy (KE) stage of advancement and its relationship to the completion of the effectiveness of the long jump (Journal of the College of Basic Education, 2022)
-1 To identify the values ​​of kinetic energy rates( Enregy kinetic) at the stage of advancement of the members of the research sample. -2 Relationship recognition rates kinetic energy values ​​(Enregy kinetic) at the stage of advancement on the completion of the long jump with members of the research sample.The researchers conducting the final field experience on a sample of (6) and Athbyn department teaching students for the academic year 2011/2010 and representing the best achievement level effectively long jump among their peers and for all stages were chosen intentional way.Variables of the study: -1 Horizontal velocity phase advancement (Vx). 2 - vertical speed stage for the Advancement of (Vy). 3 - the outcome of the values ​​of speed phase advancement Vr. 4 - horizontal kinetic energy in the promotion phase (KEX). 5 - vertical kinetic energy to the stage of advancement (KEY).6 - the outcome of the values ​​of the kinetic energy at the stage of advancement (KER).The researchers reached the following conclusions:1 - the emergence of a correlation between the outcome of the values ​​of the kinetic energy at the stage of advancement( KER) and the level of achievement.2 - The emergence of a correlation between the value of horizontal kinetic energy at the stage of advancement (KEX) and the level of achievement. 3 - do not see a correlation between the value of the kinetic energy of the vertical at the stage of advancement (KEY) and the level of achievement.The researchers study suggest the following:1 - is necessary taking into account the gentlemen trainers, supervisors and teachers on the development of the values ​​of the kinetic energy of the Agafzen in their training exercises similar to the performance of the stage for the Advancement in the long jump because of their impact in improving the level of achievement. -2 Use Video between now and then in performance skills exercises and special tests for the purpose of analysis and development of a database for each hopped to determine the strengths and weaknesses in the level of performance which in turn leads to improved achievement.